2010
DOI: 10.1111/j.1745-4557.2010.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Description and Quality Evaluation of Sweet Cherries Cultured in Spain

Abstract: Several physical, chemical and color characteristics of 20 sweet cherry cultivars cultured in Spain were investigated during a 3-year (2004-06) period. A total of 26 descriptors, mainly defined by the International Plant Genetic Resources Institute and the International Union for the Protection of New Varieties of Plants were used to describe and compare the fruit quality of the main Spanish sweet cherry cultivars for fresh consumption and for industrial use. Some of the studied cultivars showed distinctive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 23 publications
5
42
0
2
Order By: Relevance
“…Cordeiro et al (2008) indicated that improved varieties have short peduncles. However, according to Perez-Sanchez et al (2010), local varieties generally had long fruit peduncles, which made harvesting more difficult. This was confirmed in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cordeiro et al (2008) indicated that improved varieties have short peduncles. However, according to Perez-Sanchez et al (2010), local varieties generally had long fruit peduncles, which made harvesting more difficult. This was confirmed in our study.…”
Section: Resultsmentioning
confidence: 99%
“…The fruit size is an important characteristic for commercial market value (Vittrup Christensen, 1995). Perez-Sanchez et al (2010) indicated that fruit weight is the most important physical attribute of the fruit, upon which the fruit value (price) depends. Table 4 shows the data for the average fruit weight of evaluated varieties.…”
Section: Resultsmentioning
confidence: 99%
“…Pérez-Sánchez et al (2010) indicated that fruit weight is the most important physical of the fruit, upon which the fruit value (price) depends. Fruit size from the trees on 'Gisela 5' rootstock depends on crop load and soil moisture (Vercammen 2002;Vercammen et al, 2006).…”
Section: Reproductive Growth Potentialmentioning
confidence: 99%
“…Celeste are symmetrical and kidney shaped. Differences in the fruit form are interesting, since a flattened sweet cherry seems to be more tempting than a lengthened one (Pérez-Sánchez et al 2010).…”
Section: Fruit Physical Featuresmentioning
confidence: 99%
“…The health benefits of cherry fruit are usually attributed to their chemical composition, since they are a good source of antioxidant compounds and other phytochemicals such as sugars, organic acids, minerals, etc. (Nagy et al 2008;Pérez-Sánchez et al 2010). …”
mentioning
confidence: 99%